Diskursus Hudûd dalam Studi Hukum Islam (Melacak Evolusi Rumusan Hudûd) - Junaidi Abdillah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2018)
The formulation of hudûd law has been more synonymous with criminal and punishment forms. Such formulations and construct are recognized to distort the true concept of hudûd. It also implicates on the theoretical debate in Islamic penal law. The main goal of this paper is to explore and elaborate the hudûd discourse in the study of Islamic law. This paper is a library research with a hermeneutical approach. The data collection technique used in this research is a documentary study (historical) which is elective-eliminative historic in nature. The analysis methods used in the research are the general methodical elements such as interpretation and deductive-inductive also personal reflection. This paper produces several conclusions: (1) The discourse of hudûd penal in the Islamic criminal law studies has experienced a paradigm shift as a dynamic entity from time to time. And the stipulation of hudûd penal is an Islamic Juristic formulation (fuqahā’) and (2) As a product of ijtihad, stipulation of hudûd or its existence is open with criticism using contemporary epistemology. (Rumusan hudûd yang selama ini ada lebih identik dengan bentuk pidana dan hukuman. Rumusan dan konstruksi yang demikian diakui telah mendistorsikan konsep sebenarnya tentang konsepsi hudûd. Paper ini bertujuan mengupas serta mengelaborasi diskursus hudûd dalam studi hukum Islam. Disamping itu, tulisan ini juga melacak pergeseran- paradigma terkait konsepsi dan rumusan hudûd yang muncul sepanjang sejarah. Tulisan ini menggunakan pendekatan hermeneutika-tematis melalui studi dokumenter bersifat historis elektif-eliminatif.  Data akan dibandingkan, dianalisis serta disaring hingga tersisa satu teori yang paling relevan. Paper ini menyimpulkan bahwa diskursus hudûd dalam hukum Islam telah mengalami pergeseran paradigma (paradigm shift) dari waktu ke waktu. Dan, rumusan hudûd yang identik dengan bentuk-bentuk pidana (al-ꞌuqûbât al-muqaddarah) merupakan ijtihad para fuqahâ’ atas tradisi kenabian (Sunnah). Sebagai hasil ijtihad, rumusan hudûd yang ada merupakan ruang ilmu yang terbuka dengan kritik)